OVERVIEW OF CHEST RADIOGRAPH AND CLINICAL SYMPTOMS OF PEDIATRIC PULMONARY TUBERCULOSIS PATIENT IN PROF. DR. I.G.N.G NGOERAH HOSPITAL JANUARY 2021 – JUNE 2022 - Angelina, Vioreli; Ayusta, I Made Dwijaputra; Anandasari, Pande Putu Yuli; Patriawan, Putu (E-Jurnal Medika Udayana, 2023)
Tuberculosis (TB) is an infectious disease whose incidence is still quite high in Indonesia. The increasing incidence of pediatric pulmonary TB is still happening today. The diagnosis of pediatric pulmonary TB is still a hot topic because the chest radiograph and clinical symptoms are not typical and are often found in other diseases. The aim of the research is to know the overview of chest radiograph and clinical symptoms of pediatric pulmonary TB patients. This research was conducted at Prof. RSUP. Dr. I.G.N.G Ngoerah January 2021 – June 2022 using a cross-sectional descriptive method and medical record data as source with total sample is 30 people. Univariate analysis was performed using the Statistical Package for the Social Science (SPSS) version 26.0 for MacOS. The results of the study are majority of pediatric pulmonary TB patients at RSUP Prof. Dr. I.G.N.G Ngoerah January 2021 – June 2022 is female (60%), age group 11-16 years (50%), abnormal chest radiograph (96.7%), asymptomatic (63.3%), lymphadenopathy of hilar/paratracheal lymph nodes with/without parenchymal consolidation (96.7%), cough symptoms (30%). Children with pulmonary TB at RSUP Prof. Dr. I.G.N.G Ngoerah January 2021 – June 2022 is dominated by female gender, age group 11-16 years, abnormal chest radiograph, asymptomatic, lymphadenopathy of hilar/paratracheal lymph nodes with/without parenchymal consolidation and symptoms of cough.